Anti-tumor activities of probiotics in cervical cancer - Moghaddaseh Jahanshahi; Parisa Maleki Dana; Bita Badehnoosh; Zatollah Asemi; Jamal Hallajzadeh; Mohammad Ali Mansournia; Bahman Yousefi; Bahram Moazzami; Shahla Chaichian (Journal of Ovarian Research, 2020)
Abstract Cervical cancer is considered as an important malignancy among women worldwide. Currently-used treatments of cervical cancer are reported to be cytotoxic for patients. Moreover, these therapies have shown some side effects which can negatively affect the lives of women suffering from this cancer. Therefore, there is need for anti-tumor agents that are less toxic than common therapeutic drugs. Besides, applying agents for preventing or reducing the side effects of cervical cancer therapies can be effective in improving the life quality of cervical cancer patients. Studies have shown that probiotics have several effects on biological processes. One of the most prominent aspects in which probiotics play a role is in the field of cancer. There are multiple studies which have focused on the functions of probiotics in diagnosis, prevention, or treatment of cancer. Besides their direct anti-tumor activities, probiotics can be used as an additional agent for enhancing or modulating other diagnostic and therapeutic methods. Herein, the effects of probiotics on cervical cancer cells are discussed, which may be useful in the prevention and treatment of this cancer. We review the studies concerned with the roles of probiotics in modulating and reducing the gastrointestinal adverse effects caused by cervical cancer therapies. Furthermore, we cover the investigations focusing on the combination of probiotics with other drugs for diagnosis or treatment of cervical cancer.